EXPERIMENTAL STUDY OF ANTI-THROMBOTIC ACTIVITY OF PENTOXYFILLIN MICROPARTICLES: BASED ON POLY-DL-LACTIDE-CO-GLYCOLIDE IN COMPARISON WITH PENTOXYFILLIN - T. V. Timchenko; V. E. Pogorelyi; A. V. Voronkov; L. M. Makarova; L. I. Scherbakova; V. A. Kompantsev; A. I. Medvetskyi; A. Y. Platonova (Фармация и фармакология (Пятигорск), 2019)
The aim of the work was a comparative experimental study of the effect of oral administration of Pentoxifylline microparticles based on PLGA, and “standard” Pentoxifylline, on the ADP-induced platelet aggregation process in rats.Materials and methods. Pentoxifylline substance (100 mg/kg) was used as a reference drug, and PLGA-based Pentoxifylline microparticles with an average dynamic radius of 175.4 nт were used as the object in study. In the experiment, male Wistar rats (m = 300–330 g), the same age group (9 months) were used. They were divided into 3 groups, each of 6 animals. The antiplatelet activity was assessed by determining the degree and rate of platelet aggregation in 1, 3, 5, 8 and 24 hours after a single oral administration of the reference drug and the object under study. Adenosine diphosphate (ADP) at the concentration of 5 μM was used as an aggregation inducer. The aggregation process was recorded using a two-channel laser platelet aggregation analyzer ALAT-2, wavelength of 0.785 μm. by determining the average conventional size of the aggregates.Results. The experiment has proved the following: PLGA-based Pentoxifylline microparticles are more effective at reducing the possibility of platelets to aggregate within 24 hours of the investigation (more than 40%) conventional to the control group value. Besides, it should be noted that according to the effectiveness of the pharmacological action during AD-induced platelet aggregation, the microparticles are commensurate with the standard sample - Pentoxifylline. The action of the microparticle object under study lasts for 24 hours, while the effect of the reference drug is over after 3 hours and then the indicators of the reference group do not differ from those of the control onel.Conclusion. When administered per os, PLGA-based Pentoxifylline microparticles prolong the pharmacological effect significantly – up to 24 hours.